LncRNA-ANRIL regulates CDKN2A to promote malignant proliferation of Kasumi-1 cells - Jianxia Xu; Jingxin Zhang; Chengsi Zhang; Huali Hu; Siqi Wang; Fahua Deng; Wu Zhou; Yuancheng Liu; Chenlong Hu; Hai Huang; Sixi Wei (Cell Division)
Abstract Objective This study aimed to investigate the regulatory effects of long non-coding RNA-ANRIL on CDKN2A in the cell cycle of Kasumi-1 cells and elucidate the underlying molecular mechanisms. Methods ANRIL and CDKN2A expression levels were quantified using RT-qPCR in peripheral blood samples from acute myeloid leukemia (AML) patients. CDKN2A knockdown efficiency was validated via RT-qPCR, and cell cycle distribution was analyzed using flow cytometry. Cell proliferation assays were conducted with CCK-8 following palbociclib treatment and CDKN2A downregulation. RNA immunoprecipitation (RIP) identified potential ANRIL-associated targets, while western blotting assessed the expression levels of GSK3β/β-catenin/cyclin D1 signaling components and related proteins. Results ANRIL and CDKN2A were markedly overexpressed in AML patient samples. Knockdown of ANRIL and CDKN2A led to G1 phase arrest accompanied by reduced CDK2/4/6 and cyclin D1 protein levels, while ANRIL upregulation induced the opposite effect. Palbociclib treatment for 24 h and 48 h elevated the G1 phase cell population and suppressed CDK2/4/6 and cyclin D1 protein expression, demonstrating its ability to counteract ANRIL-driven cell cycle progression. Downregulation of ANRIL and CDKN2A also suppressed the GSK3β/β-catenin signaling pathway, reducing cyclin D1 expression, whereas ANRIL upregulation reactivated this axis. Co-transfection experiments showed that simultaneous cyclin D1 suppression and ANRIL overexpression attenuated ANRIL’s stimulatory effects on cell cycle progression. RIP analysis confirmed a physical interaction between ANRIL and CDKN2A. Furthermore, CDKN2A downregulation inhibited cell proliferation and reversed GSK3β/β-catenin/cyclin D1 pathway activation mediated by ANRIL upregulation. Conclusion ANRIL facilitates Kasumi-1 cell survival by modulating CDKN2A to activate the GSK3β/β-catenin/cyclin D1 signaling pathway.